(3cJGH aj GdCOHs
(3ChdgG (B:s
(3PgH efg GdCWjHGf ojQGO Hg GdCcd hGdfcGM, hCedc efg GdCUaQGf s
(3BNQgG (B:s
(3ZOG QoH MSmf hGdedGoM YHjoOg adeG HOG fGOhog gPG s
(3HGdfSNI JbWjYs
(3ajg eNJGQGJ TYQjIs
(3haUhd djSJ aj GdCOH cGddZIs
(3hUaGJ CfhGY ef GdMHQs
(3hGdaQb GdOjfjIs
(3hZjQgG s
Keywords: (3GdCOHs